1994
DOI: 10.1111/j.1467-6427.1994.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Family therapy in the home

Abstract: There is good evidence in other areas of therapeutic endeavour that home-based therapy may have advantages over clinic-based work for some patients. There are some families who have real dificulties in attending clinics. Despite these facts little has been written on the topic. This brief article reviews some of the objections to home-based family work and suggests possible solutions for the interested therapist.It is a cold and gloomy night, just starting to rain. As you park the car, you are sure you can hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…argued in that ‘Home‐based services are an effective tool for working with high‐risk families who do not respond to traditional in‐office services’ (p. 403). In the home therapy literature early papers were written in the UK by Cottrell () and Messent (). Cottrell looked at issues of seating, attendance, disruptions and timing.…”
Section: Combating Access Problems Social Justice and Systemic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…argued in that ‘Home‐based services are an effective tool for working with high‐risk families who do not respond to traditional in‐office services’ (p. 403). In the home therapy literature early papers were written in the UK by Cottrell () and Messent (). Cottrell looked at issues of seating, attendance, disruptions and timing.…”
Section: Combating Access Problems Social Justice and Systemic Therapymentioning
confidence: 99%
“…Will we look foolish?’ (Frosh et al., ; Reimers et al., ). Although there are constraints in working in the home (Cottrell, ), one advantage of doing so is that we can experience the challenges the family face in their lived context. Families don't have to describe their interactional patterns or their physical environment; they show it to us.…”
Section: Permission‐seeking: a Practice Examplementioning
confidence: 99%
“…Families who experience physical barriers often lack transportation, live a considerable distance from a mental health agency, or include a family member who has physical conditions limiting mobility. Visiting the home increases access to and inclusion of family members who might not otherwise attend therapy in the office (Cortes 2004;Cottrell 1994;Schacht et al 1989;Woodford 1999;Zarski et al 1991;Zarski and Zygmond 1989). Psychological and emotional barriers are reflected when a key family member resists attending treatment in the office (Schacht et al 1989;Zarski and Fluharty 1992;Zarski and Zygmond 1989), or when family members fear and distrust social services and assume that attending therapy in an office may jeopardize the family's perceived security (e.g., immigration status).…”
Section: Indications Specific To Hbftmentioning
confidence: 99%
“…Several studies have suggested that a home-based approach has demonstrated reasonable degrees of effectiveness in addressing the following clinical issues: children identified as "seriously emotionally disturbed" or as having a "serious emotional disturbance" (Cherniss and Herzog 1996;Curtis et al 2004;Fuller 2004;Schmidt et al 2006;Sexton and Alexander 2000;Stinchfield 2004;Woodford 1999;Woolston et al 1998;Zarski and Fluharty 1992); children and adolescents exhibiting antisocial behaviors, juvenile delinquents, and those involved with Juvenile Justice Services (Cherniss and Herzog 1996;Curtis et al 2004;Sexton and Alexander 2000;Woodford 1999;Woolston et al 1998;Zarski and Fluharty 1992;Zarski and Zygmond 1989); children with autism (Cottrell 1994); children in need of foster care (Fuller 2004); and families more broadly defined as multiproblem, at-risk, or multi-challenged (Adams and Maynard 2000;Cortes 2004;Johnson et al 2002;Schacht et al1989;Slattery and Knapp 2003;Snyder and McCollum 1999;Zarski and Zygmond 1989). Each of these articles has revealed that families involved in HBFT have experienced greater benefits than those who engaged in traditional, office-based treatment approaches.…”
Section: Indications Specific To Hbftmentioning
confidence: 99%
See 1 more Smart Citation